PC (polycarbonate) composition as well as preparation method and application thereof

By introducing magnesium oxide and silica of specific sizes and whiteness into PC resins and optimizing their retained average particle size ratio, it solves the problem that traditional light transmitting agents are difficult to achieve high whiteness and high light transmittance, and achieves efficient optical and appearance performance, which is suitable for high-demand automotive parts.

CN119592038AActive Publication Date: 2025-03-11KINGFA SCI & TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411808662.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-11
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The addition of traditional light transmitting agents to PC resin cannot achieve high whiteness effect, and some catalysts will cause the PC resin to undergo yellowing effect, reducing whiteness, and it is difficult to meet the requirements of high light transmittance, infrared transmittance and high whiteness at the same time.

Method used

Magnesium oxide and silica of specific sizes and whiteness are introduced as light transmitting agents in PC resins. By optimizing the retained average particle size ratio and whiteness of the two, the yellowing effect caused by catalytic action is avoided, and high light transmittance and high whiteness are achieved.

Benefits of technology

It is achieved without the yellowing effect to obtain PC compositions with high whiteness, high light transmittance and high infrared transmittance, which meets the comprehensive material index for high light transmittance and high infrared linear automotive parts such as active air intake grilles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179965970000061
    Figure BDA0005179965970000061
  • Figure BDA0005179965970000071
    Figure BDA0005179965970000071
  • Figure BDA0005179965970000072
    Figure BDA0005179965970000072
Patent Text Reader

Abstract

The invention discloses a PC (polycarbonate) composition and a preparation method and application thereof, and belongs to the technical field of high polymer materials, magnesium oxide and silicon dioxide with specific size and whiteness are introduced into PC matrix resin to serve as a light-transmitting agent, so that the prepared product does not generate a yellowing effect, has ideal whiteness, and is high in light transmittance. And meanwhile, high light transmittance and high infrared light transmittance can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a PC composition and a preparation method and application thereof. Background Art

[0002] PC (polycarbonate) has excellent mechanical properties and flame retardant properties. It is an ideal thermoplastic engineering material and is widely used in the automotive industry. When used to prepare automotive parts with high light transmittance and high infrared transmittance, such as active air intake grilles, PC materials often need to introduce some specific organic or inorganic light-transmitting agents into the product for compounding. However, since active air intake grilles are generally white, these PC materials are also required to have a high whiteness appearance. Specifically, the materials used for such automotive parts need to have an infrared transmittance of more than 65%, a light transmittance of more than 28%, and a whiteness of more than 86, which is a comprehensive indicator.

[0003] However, adding traditional translucent agents to PC resin cannot achieve a high whiteness effect. Even some catalysts with high light transmittance or high infrared transmittance will catalyze the yellowing effect of PC resin during product processing or use, further reducing the whiteness. Summary of the invention

[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a PC composition, which introduces magnesium oxide and silicon dioxide of specific size and whiteness into a PC matrix resin as light-transmitting agents, so that the prepared product will not have a yellowing effect, has an ideal whiteness, and can achieve high light transmittance and high infrared transmittance.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A PC composition comprising the following components in parts by weight:

[0007] 100 parts of PC resin, 0.1-1.2 parts of magnesium oxide and 0.2-2.5 parts of silicon dioxide;

[0008] The whiteness of the magnesium oxide is ≥95%;

[0009] The ratio of the retained average particle size of the silicon dioxide to that of the magnesium oxide is (2-7):1.

[0010] Different translucent fillers have different infrared transmittance wavelengths and different refractive indices, and their whiteness will also be different. Therefore, when applied to the PC resin matrix, the prepared products will have completely different light transmittance, light transmittance performance and appearance whiteness. At the same time, some translucent fillers will cause PC resin to turn yellow due to their own catalytic effect, affecting the appearance whiteness of the product. On the other hand, the light transmittance of the translucent filler is also related to its own particle size. Products prepared with fillers of different sizes will also have different light transmittance and infrared transmittance. Based on the above situation, there is still no PC composite material specifically suitable for active air intake grilles with high whiteness, high light transmittance and high infrared transmittance. To this end, the technical solution of the present invention introduces a specific magnesium oxide and silicon dioxide compound into the PC resin matrix, wherein the infrared transmission wavelength of the magnesium oxide is 0.4 to 6 μm, and the refractive index is 1.736, which is very close to the refractive index of the PC resin, and the infrared transmittance and light transmittance are high. When the high whiteness and high scattering rate silicon dioxide act as a light transmitting agent, the PC resin will not turn yellow due to the catalytic effect. At the same time, the whiteness of the magnesium oxide is limited to at least 95% and the two different fillers are maintained within a specific range of the retained average particle size ratio. Under the condition of maintaining a relatively high whiteness, the final prepared product has an ideal light transmittance and infrared transmittance, which fully meets the comprehensive material indicators of the infrared transmittance reaching more than 65%, the light transmittance reaching more than 28%, and the whiteness reaching more than 86 when used to prepare automotive parts with high light transmittance and high infrared transmittance such as active air intake grilles.

[0011] Preferably, the PC composition comprises the following components in parts by weight:

[0012] 100 parts of PC resin, 0.2-1 parts of magnesium oxide and 0.5-2 parts of silicon dioxide.

[0013] Preferably, the PC composition comprises a PC matrix resin and a filler, and the filler comprises magnesium oxide and silicon dioxide.

[0014] More preferably, in the PC composition, the mass content of the PC resin is ≥90wt%.

[0015] Preferably, the ratio of the retained average particle size of silicon dioxide to magnesium oxide is one or two of the range values ​​of 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.2:1, 4.5:1, 4.8:1, 5:1, 5.2:1, 5.5:1, 5.8:1, 6:1, 6.2:1, 6.5:1, 6.8:1, and 7:1.

[0016] The retained average particle size of magnesium oxide and silicon dioxide in the PC composition of the present invention is the average particle size of magnesium oxide and silicon dioxide retained in the product after the specified PC composition is melt-extruded and granulated.

[0017] Preferably, the ratio of the retained average particle size of silicon dioxide to magnesium oxide is (2.3-4.2):1.

[0018] When the ratio of the retained particle sizes of the two fillers is preferably within the above range, the obtained product can achieve better whiteness and light transmittance.

[0019] Preferably, in the PC composition, the retained average particle size of magnesium oxide is 0.8 to 2.2 μm.

[0020] More preferably, the retained average particle size of the magnesium oxide is in the range of one or any two of 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, and 2.2 μm.

[0021] Preferably, in the PC composition, the retained average particle size of the silicon dioxide is 3 to 8 μm.

[0022] More preferably, the retained average particle size of the silica is within the range of one or any two of 3 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5 μm, 6 μm, 7 μm, 7.2 μm, 7.5 μm, 7.8 μm, and 8 μm.

[0023] In the technical solution of the present invention, the test method for the retained average particle size of magnesium oxide and silicon dioxide is: the PC composition is calcined at 800° C. in air for 30 minutes, the remaining ash is ultrasonically dispersed in water for 20 minutes, and then the magnesium oxide and silicon dioxide are screened by elemental analysis under a scanning electron microscope. Finally, the particle size measurement software is used to measure the particle size of at least 50 magnesium oxide particles and 50 silicon dioxide particles, and finally the average value is calculated to confirm the retained average particle size.

[0024] Preferably, in the PC composition, the magnesium oxide is light magnesium oxide, and the average particle size of the magnesium oxide is 2 to 3 μm.

[0025] Preferably, in the PC composition, the average particle size of silicon dioxide is 7 to 15 μm.

[0026] The above average particle sizes of magnesium oxide and silicon dioxide refer to the initial average particle sizes of the two fillers before the PC composition is melt-extruded and granulated. Since the initial particle sizes and hardnesses of the two filler particles are different, the average particle sizes retained after melt-extrusion and granulation are also different.

[0027] Preferably, the whiteness of the magnesium oxide is 95-99%.

[0028] More preferably, the whiteness of the magnesium dioxide is in the range of one or any two of 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%.

[0029] Further preferably, the whiteness of the magnesium oxide is ≥96%.

[0030] The effect of magnesium oxide of different whiteness on the infrared transmittance of the product varies. After optimization, the use of magnesium oxide of the above preferred whiteness can make the prepared PC composition have a higher infrared transmittance.

[0031] Preferably, the whiteness of the silicon dioxide is ≥ 99%.

[0032] Preferably, the whiteness of the magnesium oxide and silicon dioxide is tested by direct testing using a whiteness meter.

[0033] The specific test method is to use the WGB-2A desktop whiteness meter produced by Shanghai Precision Instruments, put a light-shielding black tube on the measuring space in advance and adjust the zero value with the instrument zero adjustment potentiometer. After the instrument zero position is stable, remove the black tube; put the standard whiteness plate on it and adjust the standard whiteness value with the instrument calibration potentiometer to calibrate the instrument, and then remove the standard whiteness plate; measure the sample to be tested to determine the whiteness value.

[0034] Preferably, the mass ratio of magnesium oxide to silicon dioxide is (0.625-1.25):1.

[0035] When the total filler is constant, the optical properties of the product will be different if the ratio of magnesium oxide to silicon dioxide is different, especially the infrared transmittance and whiteness of the product. When it is within the above preferred range, the product can have better infrared transmittance and whiteness.

[0036] Preferably, the PC resin has a melt flow rate of 10 to 30 g / 10 min at 300° C. and a load of 1.2 kg according to GB / T 3682-2000.

[0037] More preferably, the melt flow rate of the PC resin at 300° C. and a load of 1.2 kg is in the range of one or any two of 10 g / 10 min, 12 g / 10 min, 15 g / 10 min, 18 g / 10 min, 20 g / 10 min, 22 g / 10 min, 25 g / 10 min, 28 g / 10 min, and 30 g / 10 min.

[0038] More preferably, the PC resin is bisphenol A type PC resin.

[0039] Preferably, the PC composition further comprises 0.1 to 5 parts of a functional additive;

[0040] Further preferably, the functional additives include but are not limited to at least one of an antistatic agent, an antibacterial agent, a hydrolysis-resistant agent, an antioxidant, an anti-ultraviolet agent, and a lubricant. A person skilled in the art may add various functional additives according to actual needs without affecting the expected performance of the PC composition of the present invention. For example, in order to make the PC composition antistatic during application, a person skilled in the art may add an antistatic agent to the product; in order to make the PC composition have a better demoulding effect during processing, a person skilled in the art may add a small amount of lubricant to the product for lubrication.

[0041] Another object of the present invention is to provide a method for preparing the PC composition, comprising the following steps:

[0042] The components are added into a screw extruder for melt extrusion and granulation to obtain the PC composition.

[0043] Preferably, the temperature zones of the screw extruder are set to 270-290°C in zone 1, 270-290°C in zone 2, 280-260°C in zone 3, 280-260°C in zone 4, 280-260°C in zone 5, 270-260°C in zone 6, 270-260°C in zone 7, 265-250°C in zone 8, 260-240°C in zone 9, and 260-240°C in zone 10, the screw speed is 300-500rpm, and the screw aspect ratio is (45-50):1.

[0044] Another object of the present invention is to provide application of the PC composition in the preparation of white automobile parts.

[0045] Preferably, the automobile parts include at least one of an active air intake grille, a head-up display, and a radar cover.

[0046] The PC composition of the present invention can make the prepared product have high light transmittance, high infrared transmittance and high whiteness based on the selection of inorganic fillers and the optimized design of the combination, and is very suitable for the preparation of automotive parts with extremely high requirements for optical properties and appearance properties.

[0047] The beneficial effect of the present invention is that the present invention provides a PC composition, which introduces magnesium oxide and silicon dioxide of specific size and whiteness into a PC matrix resin as light-transmitting agents, so that the prepared product will not have a yellowing effect, has an ideal whiteness, and can achieve high light transmittance and high infrared transmittance. DETAILED DESCRIPTION

[0048] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0049] Examples 1 to 15

[0050] An embodiment of a PC composition and a preparation method and application thereof according to the present invention, the components of the PC composition are shown in Table 1.

[0051] The preparation method of the PC composition comprises the following steps:

[0052] The components are mixed uniformly, and then melt-extruded and granulated in a twin-screw extruder to obtain the PC composition.

[0053] When the components are melt-extruded, the temperature zones of the screw extruder are set to 280°C in zone 1, 280°C in zone 2, 270°C in zone 3, 270°C in zone 4, 270°C in zone 5, 265°C in zone 6, 265°C in zone 7, 260°C in zone 8, 250°C in zone 9, and 250°C in zone 10, the screw speed is 500rpm, and the screw aspect ratio is 48:1.

[0054] Comparative Examples 1 to 9

[0055] The difference between the comparative examples and the embodiments is only in the types and proportions of components, as shown in Table 2.

[0056] Among the components described in each embodiment and comparative example,

[0057] PC resin 1 is 1300-22NP produced by LG of South Korea, with a melt flow rate of 20g / 10min at 300℃ and 1.2kg load;

[0058] PC resin 2 is 1300-10NP produced by LG, South Korea, with a melt flow rate of 10 g / 10 min at 300 °C and 1.2 kg load;

[0059] Magnesium oxide 1 is light magnesium oxide YY-4 produced by Hebei Meishen Technology Co., Ltd., with an average particle size of 2μm and a whiteness of 97% after screening;

[0060] Magnesium oxide 2 is light magnesium oxide YY-1 produced by Hebei Meishen Technology Co., Ltd., with an average particle size of 2μm and a whiteness of 96% after screening;

[0061] Magnesium oxide 3 is light magnesium oxide YY-1 produced by Hebei Meishen Technology Co., Ltd., with an average particle size of 3μm and a whiteness of 96% after screening;

[0062] Magnesium oxide 4 is 90a type light magnesium oxide produced by Yingkou Zhongwei Refractory Material Co., Ltd., with an average particle size of 3 μm and a whiteness of 95%;

[0063] Magnesium oxide 5 is 87a type light magnesium oxide produced by Yingkou Zhongwei Refractory Material Co., Ltd., with an average particle size of 3 μm and a whiteness of 94%;

[0064] Silica 1 is MT-10 produced by Deshan Chemical Industry, with an average particle size of 7 μm and a whiteness of 99% after screening;

[0065] Silicon dioxide 2 is MT-10 produced by Deshan Chemical Industry, with an average particle size of 15 μm and a whiteness of 99% after screening;

[0066] Silicon dioxide 3 is MT-10 produced by Deshan Chemical Industry, with an average particle size of 12 μm and a whiteness of 99% after screening;

[0067] Silica 4 is HM-30S produced by Deshan Chemical Industry, with an average particle size of 7 μm and a whiteness of 99%;

[0068] Zinc oxide 1 is DXN-TS2000 produced by Darcynon, with an average particle size of 3μm and a whiteness of 99%;

[0069] Zinc oxide 2 is ZnO-4 produced by Shenyang Longrun Fine Chemical Raw Materials Co., Ltd., with an average particle size of 15 μm and a whiteness of 90%;

[0070] Magnesium fluoride is produced by Wuhan Kemik Biomedical Technology, with an average particle size of 3μm and a whiteness of 98%;

[0071] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0072] It should be noted that the retained average particle sizes of magnesium oxide and silicon dioxide in the PC compositions of the embodiments and comparative examples of the present invention are confirmed by directly testing the products after preparation using the aforementioned method, and the corresponding parameter values ​​of the raw materials used are not used.

[0073] In Table 1, M represents the numerical value of the ratio of the retained average particle sizes of silicon dioxide and magnesium oxide.

[0074] Table 1

[0075]

[0076]

[0077] Table 2

[0078]

[0079] In order to verify the performance of the PC composition of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:

[0080] (1) Infrared transmittance: The products obtained in each embodiment and comparative example were injection molded into test specimens of 125×13×1 mm, and then the infrared transmittance was tested by scanning the infrared light wavelength range of 780 to 1650 nm using an Iambda 950 UV-visible infrared spectrophotometer;

[0081] (2) Transmittance test: The products obtained in each embodiment and comparative example were injection molded into test specimens of 50×50×1.6 mm, and then tested according to GB / T 2410-2008;

[0082] (3) Whiteness test: The products obtained in each embodiment and comparative example were injection molded into test specimens of 5×100×100 mm, and then tested according to GB / T 2913-1982.

[0083] The test results are shown in Tables 3 and 4.

[0084] Table 3

[0085]

[0086] Table 4

[0087]

[0088] It can be seen from Table 3 and Table 4 that the PC compositions of the embodiments of the present invention have ideal optical properties and appearance properties, the infrared transmittance can reach more than 67%, specifically in the range of 68-72%, and the light transmittance can reach more than 29%, specifically in the range of 30-35%, and the whiteness can reach more than 87%, which meets the comprehensive indicators of the materials used for such automotive parts, that is, the infrared transmittance reaches more than 65%, the light transmittance reaches more than 28%, and the whiteness reaches more than 86. The main reason why the product can achieve this comprehensive effect is that the product introduces two fillers with specific retained particle size ratios as colorants and translucent agents into the PC resin matrix.

[0089] In contrast, the fillers in the products of Comparative Examples 1 and 2 are only magnesium oxide or silicon dioxide, and the optical properties of the two products are not up to standard, and the whiteness of the product of Comparative Example 1 is low and cannot meet the appearance requirements; the ratio of the retained average particle size of magnesium oxide and silicon dioxide in the products of Comparative Examples 3 and 7 does not meet the scope of the products of the present invention, and the products do not meet the standards in terms of light transmittance and whiteness. At the same time, the infrared transmittance of the product of Comparative Example 7 is also low, with a maximum of only 60%; when magnesium oxide is selected, the whiteness of the product of Comparative Example 4 does not reach 95%, which not only makes the whiteness of the product low, but also reduces the light transmittance compared with the example product, and cannot meet the standard requirements; in addition, in Comparative Examples 5 and 6, the magnesium oxide in the products is replaced by zinc oxide and magnesium fluoride, two light-transmitting agents often added to traditional resins. However, since the refractive index and light transmittance of these two components are different from those of magnesium oxide, and the latter may even induce a yellowing reaction of the PC resin after contacting the PC resin, the whiteness of the final products is low, and the light transmittance and infrared transmittance cannot reach the level of the example product. If the silicon dioxide in the product is replaced, as shown in Comparative Example 9, although the whiteness of the product is higher, the optical properties are poor.

[0090] According to Examples 4 to 10 and Example 15, it can be seen that the optical properties and whiteness of the prepared products vary due to the different ratios of the retained average particle sizes of magnesium oxide and silicon dioxide. When the preferred ratio is in the range of (2.3 to 6): 1, the infrared transmittance of the product can reach 70% or more, and the whiteness can reach 90% or more.

[0091] It can be seen from Example 4 and Examples 11 to 14 that when the ratio of the retained particle sizes of magnesium oxide and silicon dioxide is relatively stable, the addition ratio of the two will also affect the performance of the product. When the ratio is preferably (0.625 to 1.25): 1, the comprehensive performance of the product is better.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A PC composition, characterized in that The composition comprises the following components in parts by weight: 100 parts of PC resin, 0.1-1.2 parts of magnesium oxide and 0.2-2.5 parts of silicon dioxide; The whiteness of the magnesium oxide is ≥95%; The ratio of the retained average particle size of the silicon dioxide to that of the magnesium oxide is (2-7):

1.

2. The PC composition according to claim 1, characterized in that In the PC composition, the retained average particle size of magnesium oxide is 0.8 to 2.2 μm.

3. The PC composition according to claim 1, characterized in that In the PC composition, the retained average particle size of the silicon dioxide is 3 to 8 μm.

4. The PC composition according to claim 1, characterized in that The whiteness of the magnesium oxide is 95-99%.

5. The PC composition according to claim 1, characterized in that: The mass ratio of the magnesium oxide to the silicon dioxide is (0.625-1.25):

1.

6. The PC composition according to claim 1, characterized in that: The PC resin has a melt flow rate of 10 to 30 g / 10 min at 300° C. and a load of 1.2 kg according to GB / T3682-2000.

7. The method for preparing the PC composition according to any one of claims 1 to 6, characterized in that: The following steps are involved: The components are added into a screw extruder for melt extrusion and granulation to obtain the PC composition.

8. Use of the PC composition according to any one of claims 1 to 6 in the preparation of white automobile parts.

9. The use according to claim 8, characterized in that The automobile parts include at least one of an active air intake grille, a head-up display, and a radar cover.

10. An automobile component, characterized in that: The PC composition comprises the PC composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Stress cracking-resistant PC (Polycarbonate) material and preparation method thereof

    CN109666278A

  • High-transparency PC (polycarbonate) composition as well as preparation method and application thereof

    CN116120728A

  • High-whiteness and high-transmittance PCR (Polymerase Chain Reaction) polymer composite material, and preparation method and application thereof

    CN118290920A

  • Amorphous silica-alumina spherical particles and process for preparation thereof

    US5139760A